UJI EFEKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN PEPAYA (Carica papaya L.) PADA SEDIAAN KRIM TERHADAP DPPH (1,1-diphenyl-2-picrylhydrazil) - ., Andi (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2014)
Abstract: Free radicals are one of the causes of the premature aging. free radicals can besuppressed by antioxidants. Carica papaya (Carica papaya L.) is one of the plants that potentiallyas a natural antioxidant. Ethanol extract of papaya leaves have IC 50 0.58 mg / ml, but not knownin cream. This study aims to determine the IC50 of the ethanol extract of papaya cream using DPPH(1,1-diphenyl-2-pikrilhidrazil) method. The extraction was done by maceration using ethanol.Ethanol extract of papaya leaves were obtained is tested phytochemicals, qualitative test withDPPH and qualitative test of vitamin C with KMnO4. The results of phytochemical screening wereknown that contains alkaloids, flavonoids, steroids, and phenolic. The results qualitative DPPHantioxidant activity and qualitative Vitamin C with KMnO4 showed have antioxidant activity andvitamin C. Ethanol extract prepared in cream. pH and particle size of cream were good. Creamingoccurs in formulas 4 and the most preferably cream is formula 1. Quantitative test of the ethanolextract of papaya cream using visible spectrophotometry. The results of spectrophotometricmeasurements showed that the ethanol extract of leaves papaya cream has a weak antioxidantactivity with IC50Keywords: Papaya Leaf, Antioxidants, Ethanol Extracts, DPPH